Competency Mapping of Engineers in the Engineering Industry of Satara, Maharashtra - Yadav, Deepti Manohar; Nalawade, Krishnaji Mahadeo (Prabandhan: Indian Journal of Management, 2012)
This paper aims to examine the development of engineers' competency model in the engineering industry and its importance towards the present context of human capital and management functions in Engineering units in Satara, Maharashtra. 118 engineering units from the industrial area of Satara, Maharashtra were considered as a sample for the study. Stratified sampling survey was made from the small, medium and large scale engineering units in the industrial area of Satara, Maharashtra. The research was conducted during the period from June 2010-2011. The results of the research show that only 27.78% of the engineering units were implementing the competency mapping concept and 60% of the engineering units were at the initial stage of implementation. The paper describes a linear competency model for engineers, with a list of competencies according to their type and requirement level in a job. If engineering organizations use competency models, conduct research at the organizational level, renew the model with changing needs, include all human resource procedures, organizational levels and provide training to employees, then the engineering units will grow in talent and knowledge management.